Analysis of Nursing Staff as a Basis for Human Resource Management Policy Formulation at Hospital X Tangerang - Wulandari, Vika; Rakhman, Sitti (Sean Institute, 2025)
Stress is a psychological response commonly experienced by individuals when facing internal or external pressures. Measuring stress levels among nurses is essential to understand their mental condition and ensure task performance is maintained. This descriptive quantitative study aimed to assess the stress levels of nurses at Hospital X in Tangerang over the past month using the Perceived Stress Scale (PSS-10). The study involved a total population of 20 nurses, with data collected through a 10-item Likert-scale questionnaire. Descriptive analysis was used to determine the frequency and percentage of stress levels. Results showed that 55% (11 respondents) experienced low stress, while 45% (9 respondents) had moderate stress, with an average score of 14, a minimum of 7, and a maximum of 25. These findings highlight the need for effective stress management strategies by hospital management to prevent worsening stress and to enhance nurse productivity.